We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
806
1
avatar

How do you solve 2(x-3) + 5x = 4(x+2) - 5 ?

 May 19, 2015

Best Answer 

 #1
avatar+981 
+5

 

2(x - 3) + 5x = 4(x + 2) -5 ..... Expand

 

2x - 6 + 5x = 4x + 8 -5 ...... Collect like terms

 

7x - 6 = 4x + 3 ....... Simplify

 

3x = 9

 

x = 3

 

 

To check:

2(3-3) + 5*3 = 4(3 + 2) - 5

0 + 15 = 4*5 -5

15 = 20 - 5

15 = 15

 May 20, 2015
 #1
avatar+981 
+5
Best Answer

 

2(x - 3) + 5x = 4(x + 2) -5 ..... Expand

 

2x - 6 + 5x = 4x + 8 -5 ...... Collect like terms

 

7x - 6 = 4x + 3 ....... Simplify

 

3x = 9

 

x = 3

 

 

To check:

2(3-3) + 5*3 = 4(3 + 2) - 5

0 + 15 = 4*5 -5

15 = 20 - 5

15 = 15

zacismyname May 20, 2015

11 Online Users